Living together before compared to after marriage impacts on marital satisfaction - Mendoza, Mikael Carlos A.; Sayo, Leiko (College of Home Economics, University of the Philippines Diliman, 2023)
This quantitative study examines the marital satisfaction of couples who engaged in premarital cohabitation and compared it to those that engaged in postmarital coresidence. A total of 60 Filipinos who were all married for two to seven years and live in the National Capital Region (NCR) were gathered to participate in the study. The respondents were divided into two groups: (a) married individuals who cohabited prior to marriage and (b) married individuals who lived together after marriage. They then answered the Couples Satisfaction Index (CSI-32) developed by Funk and Rogge to measure their marital satisfaction. An independent samples t-Test was used to analyze the data and compare the mean scores of the two groups. The findings revealed that the average marital satisfaction scores between the two groups were statistically different. Particularly, couples who lived together before marriage exhibited significantly higher marital satisfaction. They also scored higher averages in terms of their functionality, intimacy and togetherness, security and commitment, and fulfillment as a couple. In sum, these results are consistent with The Practical Experience of Cohabitation, a theory which posits that living together before marriage enables the couple to learn how to better live with their partner, ultimately increasing their marital satisfaction. The findings also contrast numerous other theories and past studies that associate premarital cohabitation with negative marital outcomes and poor long-term commitment.